Nab-paclitaxel monotherapy in patients with metastatic breast cancer with visceral crisis: evaluation of efficacy and tolerability in clinical practice - L. Yu. Vladimirova; K. A. Novoselova; N. A. Abramova; I. L. Popova; N. M. Tikhanovskaya; L. A. Ryadinskaya; A. A. Lyanova; M. O. Ezhova; M. A. Teplyakova; A. A. Tishina; E. V. Prikhodko (Медицинский совет, 2019)
The authors analysed the efficacy and safety of Nab-paclitaxel (Nab-R) monotherapy in patients with metastatic breast cancer with visceral crisis (VC) in the second- and further-line chemotherapy. The objective response rate (ORR) was 35.3% (6 of 17 persons). The most frequent side effects were general weakness, nausea, symptoms of peripheral neuropathy. The degree of toxicity did not exceed 1–2 in 60% of cases. The median time to progression was 7.8 months. (95% CI 6–10.6). The median overall survival for patients with VC was 14.9 months. (95% CI 12.0–16.9). Efficacy and controlled toxicity of Nab-P allows its use in pre-treated patients, including ones with VC.